Інтегрована інформаційно-керуюча система керування вогнем для бойових броньованих машин - Оліярник, Б. О.; Бондарук, А. Б.; Мошнін, В. М.; Чайковський, Р. І. (НТУ "ХПІ", 2008)
Offers a structure of a tank control system of fire constructed by a principle of the open distributed system, which is unified as much as possible for solving the tasks of managing of tank devices. The offered structure allows on the one side at maximum to close functions and to reduce to a minimum interchange of parameters at share operation object systems work, with another side - to increase size of tasks at the expense of escalating of an amount of systems (subsystems), using thus all collection of actual parameters of the object existing in the full system.
Keywords: озброєння броньованих машин; параметри бронеоб'єкта; сигнали керування; ймовірність попадання